New Frontiers in Stellar Interferometry 2004
DOI: 10.1117/12.551435
|View full text |Cite
|
Sign up to set email alerts
|

Infrared imaging of Capella with the IOTA interferometer

Abstract: We present near infrared aperture synthesis maps of the well known binary star Capella (α Aur) produced with the upgraded IOTA interferometer on top of Mount Hopkins, Arizona. Michelson interferograms were obtained simultaneously on three interferometer baselines in the H-band between 2002 November 12 and 16. The simultaneous observation of fringes on three baselines permitted a single phase closure to be estimated along with three visibility amplitudes. Hybrid Mapping techniques were then used to reconstruct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This paper reviews progress in science and technology at the Infrared Optical Telescope Array (IOTA), since the last such review, 1 some of which is reported in the present volume. 2,3,4,5,6 Briefly, IOTA is a long-baseline optical interferometer located at the Smithsonian Institution's Whipple Observatory on Mount Hopkins, AZ. It comprises three 45-cm diameter telescopes which can be positioned at 17 stations on an L-shaped track, where the arm lengths are 15 m toward the south-east and 35 m toward the north-east.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper reviews progress in science and technology at the Infrared Optical Telescope Array (IOTA), since the last such review, 1 some of which is reported in the present volume. 2,3,4,5,6 Briefly, IOTA is a long-baseline optical interferometer located at the Smithsonian Institution's Whipple Observatory on Mount Hopkins, AZ. It comprises three 45-cm diameter telescopes which can be positioned at 17 stations on an L-shaped track, where the arm lengths are 15 m toward the south-east and 35 m toward the north-east.…”
Section: Introductionmentioning
confidence: 99%
“…Aperture synthesis map of Capella on 12-16 Nov. 2002, using one of three different reconstruction algorithms, all of which performed approximately equally well 3. …”
mentioning
confidence: 99%